The rational design of international institutions - Koremenos, Barbara; Lipson, Charles; Snidal, Duncan (Cambridge University Press, 2004)
International institutions vary widely in terms of key institutional features such as membership, scope, and flexibility. This books argues that this is so because international actors are goal-seeking agents who make specific institutional design choices to solve the particular cooperation problems they face in different issue-areas.
Previously published as a special issue of International organization, v. 55, no. 4, 2001.
Keywords: International organization.; Organisation internationale.; LAW -- International.; International organization; Internationale organisaties.; Institutionalisme.